Remote Monitoring of Cardiovascular Risks of Medical Rehabilitation of Ischemic Stroke Patients Using Information and Telecommunication Systems - Elena V. Kostenko; Lyudmila V. Petrova; Natalia V. Neprintseva; Svetlana T. Shurupova; Alla V. Kucherova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
Due to the high incidence of cerebral stroke, the relevance of the problem of medical rehabilitation for this category of patientsis beyond doubt. The increase in disability rates due to movement disorders among stroke survivors (3.2 per 100,000 population)necessitates the introduction of innovative rehabilitation technologies. Patients with cerebral stroke have a high risk of cardiocerebralcomplications, which should not limit the possibilities of medical rehabilitation. Therefore, the control of possible MR-risks is animportant organizational aspect and can be implemented through the introduction of information and communication (ICT) andtelemedicine technologies. Conducting dynamic telemetric ECG monitoring during of medical rehabilitation allows to prevent thedevelopment of possible cardiovascular risks and personalize the medical rehabilitation program.Aim. To study the effectiveness of remote tele-ECG monitoring based on information and communication technologies for assessingthe cardiovascular risks of medical rehabilitation in patients with ischemic stroke.Material and methods. The study included 83 patients with ischemic stroke, mean age 55 [51; 57]), women - 44.6%, men - 55.4%; 42patients in the early and 41 patients in the late recovery periods of ischemic stroke. All patients underwent a complex of multimodalrehabilitation techniques to restore hand dysfunction and statolocomotor disorders, carried out sequentially during one visit. For thepurpose of dynamic control of probable cardiovascular risks, objectification of the state of the cardiovascular system, correction of theintensity and duration of rehabilitation loads, a portable information and communication technologies-based telecardiac complexwas used for ECG registration. The ECG parameters were assessed in real time, as well as the stored data on the CardioOblako service.Results and discussion. The spectrum of ECG changes in patients in the early and late recovery periods of ischemic stroke was revealed.The dependence of ECG indexes and their dynamics on the duration of ischemic stroke and its subtype was determined. Asymptomaticchanges in the form of heart rhythm disorders (14,4% - supraventricular rhythm disorders, 9,6% - ventricular extrasystoles of the 1stclass), as well as repolarization processes (9,6% of cases) were registered during the course of rehabilitation measures. When discussingthe results obtained, the probable neurogenic character of cardiac rhythm and conduction disturbances as a consequence of centralneurogenic cardiovascular regulation, which is stabilized by central nervous system neuroplasticity over time, is emphasized. At thesame time, the literature indicates that these processes can be regulated by therapeutic and rehabilitative measures. In our study,correction of the intensity and duration of rehabilitation loads normalized the changes of ECG indices registered in the process ofmedical rehabilitation.Conclusion. We determined the need for a comprehensive cardiovascular risk assessment program for patients with IS with theparticipation of a therapist/cardiologist using dynamic telemetric ECG monitoring during of medical rehabilitation for the timelydetection and prevention of cardiovascular complications of medical rehabilitation, personalization of the medical rehabilitationprogram.